Synthesis, characterization of some Co(III) complexes with vic-dioxime ligands and their antimicrobial properties - Canpolat, E; Kaya, M; Gür, S (Scientific Technical Research Council Turkey, 2004)
In this study, 6 different new vie-dioxime ligands and their mononuclear complexes with Co(III) have been synthesized. The structures of these compounds were identified by using elemental analyses, IR, H-1 and C-13 NMR, electronic spectra, magnetic susceptibility measurements and conductivity. In addition, the thermal characterizations and antimicrobial activities of the ligands and their complexes have been investigated.
Keywords: vic-dioxime ligands; cobalt(III) complexes; antimicrobial activities